The Persistence of the World Religions Paradigm: Response to Jacob Barrett's "Critical Theory in World Religions: An Experiment in Course (re)Design". (31st December 2020) - Owen, Suzanne
Abstract : When I came to Leeds Trinity University, my job title was "lecturer in World Religions" and two of the modules (courses) I was to teach were called World Religions 1 and World Religions 2. There was also a separate module on Method and Theory in the Study of Religion. I was discouraged from changing these in the first couple of years partly because of market expectations. I taught them in much the way as described in Jacob's paper and in the chapters on "Subversive Pedagogies" in After World Religions (Cotter and Robertson, eds, 2016). I was aware that although we were subverting the World Religions Paradigm (WRP), we hadn't removed it. This persistence of the WRP, even when we pick it apart, concerns me. Is it really possible to teach world religions without the world religions paradigm?